Rito para crear el artificio: manifestación de la estética (meta)poética talensiana en el poema “Ceremonias” - Śmiłek, Ewa (Romanica Silesiana)
One of the poetic tendencies which developed in the Spanish poetry of the second half of the twentieth century is metapoetry. Its substantial characteristics are: auto‑reference and self‑consciousness, which appear constantly in the poetry of Generation of Novísimos. This ritual of auto‑definition and self‑creation allows these authors to implement and, at the same time, realize, the theoretical proposals of the new poetic aesthetics. Jenaro Talens, one of the representatives of this generation, demonstrates the act of poetic creation in the most explicit way. The aim of this article is to show this rite as a manifestation of the relationship between the writer, the text, the receiver and the culture of their times. It will be done by analyzing Jenaro Talens’s poem titled “Ceremonias”. Key words: ritual, Jenaro Talens, Novísimos, metapoetry, Spanish poetry